2016
DOI: 10.3389/fpubh.2016.00037
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variation in Absolute Cardiovascular Risk Assessment in Aboriginal and Torres Strait Islander People with Type 2 Diabetes

Abstract: BackgroundAbsolute cardiovascular risk assessment (CVRA) is based on the combined effects of multiple risk factors and can identify asymptomatic individuals at high risk of cardiovascular disease (CVD). Aboriginal and Torres Strait Islander people, the Indigenous people of Australia, are disproportionately affected by CVD and diabetes. Our study aimed to investigate variations in the use of absolute CVRA in patients with diabetes at Indigenous community healthcare centers and to identify patient and health cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…CVRA is particularly important in the generally healthy population as adults with known major chronic illnesses such as diabetes are at higher risk of CVD, regardless of the other risk measurements included in CVRA. Our finding that 23% of eligible clients had documented CVRA is lower than in similar studies reporting inadequate levels of screening ( 15 , 16 ) due to our exclusion of clients with chronic disease, regardless of severity. The NT had substantially higher level documentation of CVRA than other jurisdictions and of those assessed at moderate/high risk, 30% were under the age of 35 years.…”
Section: Discussioncontrasting
confidence: 86%
“…CVRA is particularly important in the generally healthy population as adults with known major chronic illnesses such as diabetes are at higher risk of CVD, regardless of the other risk measurements included in CVRA. Our finding that 23% of eligible clients had documented CVRA is lower than in similar studies reporting inadequate levels of screening ( 15 , 16 ) due to our exclusion of clients with chronic disease, regardless of severity. The NT had substantially higher level documentation of CVRA than other jurisdictions and of those assessed at moderate/high risk, 30% were under the age of 35 years.…”
Section: Discussioncontrasting
confidence: 86%
“…This study found wide variation across the participating PHC centres in the proportion of active female clients who had a cervical screening test in each two-year audit period. A high degree of between-centre variation has similarly been documented in other ABCD study investigating the variation in the delivery of other preventive care services [11,16], such as for sexually transmitted infections (STI) testing [17,18], cardiovascular care [19], and diabetes care [20]. There were a small number of the PHC centres in the current study that, for some of the years, had no documented delivery of cervical screening tests, but for half of the centres the coverage rates ranged between almost one third (29%) and two-thirds (67%) of the women who attended at least once in the past two years.…”
Section: Discussionmentioning
confidence: 93%
“…Wide variation in service delivery in Aboriginal PHC centres has been documented in previous studies of CQI in diabetes care [ 14 ], preventive care [ 19 ] and cardiovascular care [ 20 ]. In a study of CQI in diabetes care, variation reduced over audit cycles with lower performing centres showing improvements in adherence to best practice, and with a significant association between duration of CQI participation and the improvement in diabetes care processes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%